Effective safeguarding for children and young people : what next after Munro? - Blyth, Maggie; Solomon, Enver (Bristol : Policy, 2012)
This timely book takes a critical look at the impact of the Munro Review (2011) on child protection and the government's response.
Title from publisher's bibliographic system (viewed on 07 Sep 2022).
Keywords: Munro, Eileen, -- 1950-; Child welfare -- Great Britain; Child welfare -- Government policy -- Great Britain